2005
DOI: 10.1111/j.1463-5224.2005.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular peripheral nerve sheath tumor in a dog

Abstract: A tumor within the right globe in a 9-year-old Shetland sheepdog was examined pathologically. The tumor was composed of spindle or oval cells arranged in interwoven bundles with intervening collagenous or mucinous matrices. Immunohistochemically, the tumor bound antibody directed to S-100 protein and vimentin, but not to desmin, actin smooth muscle, or neurofilament. Electron microscopy revealed that the tumor cells had poorly developed cytoplasmic processes, desmosomes between closely contiguous cells, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Immunohistochemical studies have shown features most consistent with a peripheral nerve sheath tumor, specifically a schwannoma . There is a similar case reported in a yellow‐eyed cat and a similar case reported in a brown‐eyed dog . The aim of this study is to report an anterior uveal spindle cell tumor in a blue‐eyed mixed‐breed female dog.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Immunohistochemical studies have shown features most consistent with a peripheral nerve sheath tumor, specifically a schwannoma . There is a similar case reported in a yellow‐eyed cat and a similar case reported in a brown‐eyed dog . The aim of this study is to report an anterior uveal spindle cell tumor in a blue‐eyed mixed‐breed female dog.…”
Section: Introductionmentioning
confidence: 69%
“…However, the tumor may occur in any dog that presents with nonpigmented or poorly pigmented iris or ciliary body . However, it is worth mentioning that there are reports of an anterior uveal spindle cell tumor in a cat with yellow iris and an intraocular peripheral nerve sheath tumor in a brown‐eyed dog that showed features consistent with those described in SCTBED. As the origin of these tumors has not yet been fully elucidated, the correlation between the cases reported in a yellow‐eyed cat and in a brown‐eyed dog with the SCTBED remains unclear.…”
Section: Discussionmentioning
confidence: 92%
“…Other masses may show marked atypia with numerous mitoses. Intraocular hemorrhage, pre‐iridal fibrovascular membranes, and glaucoma are frequent secondary findings . Schwannomas of blue‐eyed dogs/peripheral nerve sheath tumors are immunoreactive for vimentin and S100.…”
Section: Intraocular Neoplasiamentioning
confidence: 99%
“…There is variable expression of laminin, GADD5, p53, PCNA, anti‐UVssDNA, and TERT. The neoplastic cells are immunonegative for MITF, CD34, skeletal muscle actin and TNF, and usually immunonegative for Melan‐A, smooth muscle actin and desmin . The prognosis for life for this tumor type is not well understood with only one published case of metastasis, however the prognosis for the globe is considered poor as enucleation is required in most patients …”
Section: Intraocular Neoplasiamentioning
confidence: 99%
“…Concerning the localization, PNSTs are rare in the dog and have been mainly reported in subcutaneous tissues and brachial plexuses (Koestner & Higgins 2002). Other localizations in the dog include spleen (Bergmann et al 2009), vagina (Sontas et al 2010), spinal cord (Tavasoly & Malmasy 2009), diaphragm (Anderson et al 1999), and eye (Sato et al 2005). To the best of our knowledge, primary PNSTs have not been described previously in the canine nasal cavities.…”
mentioning
confidence: 78%